Importance of developmental stage and microenvironment control in Zebrafish larvae cardiovascular studies - Patricia Fiorino; Luigi Fernandes Rosa Cauduro; Danielle Silberspitz Konig; Leonardo Fernandes Rosa Cauduro; Caio de Araujo Santos; Juliana Alves Kavai; Isadora Durigan Duarte; Anna Laura Viacava Américo (PLoS ONE, 2026)
Zebrafish ( Danio rerio ) are widely used as models in cardiovascular research due to their rapid development, optical transparency, and genetic similarity to humans. However, the lack of standardized experimental conditions, particularly regarding developmental stage and microenvironmental parameters, limits reproducibility across studies. This study aimed to characterize cardiovascular function in Zebrafish larvae and evaluate the impact of developmental stage and environmental factors. Wild-type AB embryos were maintained under standard conditions, and heart rate (HR), cardiac output (CO), and ejection fraction (EF) were measured at 24, 30, 48, 52, 56, 72, 78, and 80 hours post-fertilization (hpf). The effects of variations in temperature (27.0, 27.5, and 28.0 °C) and pH (7.0, 7.4, and 8.0) were also assessed. Results showed a progressive increase in HR from 24 to 72 hpf, stabilizing thereafter. CO exhibited two phases of elevation: an early rise between 24–48 hpf and a stronger increase between 48–56 hpf. EF remained generally stable, with a transient reduction at 48 hpf. Cardiovascular performance reached a physiologically stable state after 72 hpf, defining a reliable window for functional studies. Environmental conditions modulated these parameters: temperature variation induced approximately 20% difference in HR and reduced EF, while CO was minimally affected. In contrast, pH variations within the physiological range had no significant impact on HR, CO, or EF. These findings highlight developmental and environmental variables that may influence cardiovascular measurements in Zebrafish larvae and support the development of more consistent experimental approaches in cardiovascular and toxicological research.